Pengaruh Kaolin Terhadap Membran Blend Kitosan Poli Vinil Alkohol-Litium Sebagai Membran Elektrolit Untuk Aplikasi Baterai Ion Litium - Gonggo, Siang Tandi; Diah, Anang Wahid M.; Lanteene, Reki (Jurnal Akademika Kimia, 2017)
Today, the battery is the most practical and in expensive energy storage device in a modern community. A variety of new materials technologies has been developed in the manufacture of the battery, especially the development of the solid electrolyte (solid). Polymer Electrolytes can be found in the polymer batteries form such as lithium ion polymer battery. A natural polymer such as chitosan is potential as polymer electrolyte membrane for battery applications. The chitosan has amino and hydroxyl groups that allow for modification. The modification of chitosan membrane is expected to produce the better membranes characters. The aim of this research is to study the effect of the addition of inorganic filler kaolin on the conductivity of the polymer electrolyte that made of chitosan-polyvinyl alcohol than was added to the lithium salt. The ionic conductivity of the polymer electrolyte chitosan-polyvinyl alcohol-lithium-kaolin was measured by using an impedance spectroscopy. The measurement results showed that the polymer electrolyte chitosan-polyvinyl alcohol-lithium with the addition of 4% kaolin provide the highest ionic conductivity is large 6.551x10-5 S/cm. In comparison, characteristics of batteries that made from polymer electrolyte chitosan-polyvinyl alcohol-lithium with the addition of kaolin have a voltage of 2.4 volts which have similarities to the commercial batteries. This result indicates that the kaolin can be used as a filler to increase the ionic conductivity of the polymer electrolyte chitosan-polyvinyl alcohol-lithium, and then it can be developed as a battery.